Teacher professional learning for technology integration in mathematics classrooms through online learning communities : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Information Technology at Massey University, Albany, New Zealand - Abidin, Zaenal (Massey University, 2018)
The new school curricula in Indonesia emphasise the integration of technology into instructional practices. The infusion of technology in mathematics education requires teachers to align their teaching practices with ongoing technological innovations. Integrating technology into mathematics classrooms requires teachers to have a good knowledge of mathematics content, technology and pedagogy. Teachers also need to consider their school environments. Existing teacher professional development programmes are seen to be failing to meet teacher needs regarding content delivery that sometimes does not match the existing school conditions. The premise underlying this research is that the use of an online learning community (OLC) may present a possible solution to the current challenges. Thus, the intention of this study was to investigate the potential of OLCs to help develop teachers’ learning to fulfil their professional needs in integrating technology with the teaching of mathematics. An ethnographic approach was used to investigate the phenomenon of teacher learning within an OLC and the implementation of the new knowledge acquired in their mathematics teaching practices. Empirical data from five case studies were used to examine how participation in the OLC affected teaching practices for five teachers. The results revealed that teacher participation in an OLC offered opportunities and challenges. Teachers de-privatized their practices as they actively engaged in social learning interactions to share knowledge and help each other with the appropriate use of technology in teaching mathematics. Teachers also faced some challenges, which impeded them. These challenges included differences in school policies, such as restrictions on using social media and limited technical infrastructure, which hindered teachers from fully leveraging the OLC. Teachers with less experience in teaching with technology and with low levels of technology skills tended to be passive in the OLC. Cultural contexts revealed that lack of experience and caution about expressing opinions made teachers feel 𝘦𝘸𝘶𝘩 𝘱𝘢𝘬𝘦𝘸𝘶𝘩, a shyness in openly expressing their thoughts. Despite these barriers, the study provided evidence that teachers improvised and dealt with situations as they rose. The findings of this study provided evidence that participation in the OLC had significant impacts on teachers’ professional learning. Teachers altered their mode of using technology either as a partner or as an extension of self as they gained more confidence in their own learning. The teachers gradually transformed their participation from peripheral to full participation in promoting the use of technology for teaching mathematics. The research provides new insights into ways teachers can be helped to develop their professional learning in the use of technology for teaching mathematics through participation in OLCs. Particularly for Indonesia, the findings of this research provide an OLC-based model that could be implemented in other contexts that share similar technology landscapes and sociocultural heritages.
Keywords: Mathematics teachers; In-service training; Indonesia; Computer networks; Professional learning communities; Mathematics; Study and teaching; Mathematics; Computer-assisted instruction